PENDAMPINGAN USAHA MIKRO MECHANIC HAIRCUT DALAM PENGGUNAAN MEDIA SOSIAL INSTAGRAM DAN TIKTOK UNTUK MENINGKATKAN PELANGGAN - Fikrianto, Icho Ade; Rhefale, Muhammad Izahan Maulana; Rochmaniah, Ainur; Febriana, Poppy (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2024)
Mechanic Haircut micro business is a small business with the advantage of selling excellent services but is not yet well-known by many people. This service aimed to assist in creating creative promotional content to attract more customers by utilizing Instagram and TikTok applications. The method used in the marketing promotion consisted of 3 stages, namely observation stage, training assistance, and presentation. The community service obtained a positive result in which the activities carried out enabled the micro business owners to utilize Instagram and TikTok media as free promotional media to increase their customers. Using image editing apps and feeds containing edited images could provide recommendations for the target audience so they would be interested in becoming customers. After the service activities were carried out with good dedication and were successful in assisting Mechanic Haircut micro business, the increase in customers could be observed every day.